Emergency accesses in Dermatology Department during the Covid‐19 pandemic in a referral third level center in the north of Italy. Issue 6 (2nd September 2020) - Isoletta, Eugenio; Vassallo, Camilla; Brazzelli, Valeria; Giorgini, Chiara; Tomasini, Carlo Francesco; Sabena, Anna; Perlini, Stefano; De Silvestri, Annalisa; Barruscotti, Stefania
Abstract: During the lockdown period, most planned visits have been postponed and the number of accesses to emergency department (ED) has dramatically reduced. The aim of our study is to analyze the impact of the lockdown on the number, type, and severity of Dermatological ED diagnosis. We performed a retrospective review of all dermatological consultations in the ED of IRCSS San Matteo during the lockdown period in Italy (February 22‐May 3 2020) and compared them with those from the same period in 2019. We noticed a sharply reduction in the number of dermatological consultations requested in the ED: from 164 patients in 2019 to 33 in 2020. Some diagnostic categories showed a significant difference with a higher incidence of vasculopathic lesions (0.6% vs 12.1%, P < .0001), urticarial rashes (8.5% vs 21.2%, P = .03), and scabies (3% vs 12.1%, P = .023). We observed an increase in the proportion of patients starting medications, before coming to the ED 26.2% in 2019 vs 66.7% in 2020 ( P < .001). Furthermore, we noticed a significant increase in the average complexity of cases presenting to the ED in 2020, as proven by the increased need for biopsies and systemic therapy.